Perancangan Interior Rumah Pernikahan Pada LKP Lelly Dengan Konsep Personal White - Juli Atika; Rani Hermita; Muslida Murti (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Referring to the modern lifestyle, to carry out a wedding, there are many needs that must be prepared, so it takes a lot of time and costs quite a lot. Many vendors provide party needs, but do not provide all needs in one area. So that the bride and groom need more time, energy and money to go to different places to meet all the needs of the party, the interior design of this Wedding House adopts a concept with the title "Personal White". This concept is based on the western cultural wedding concept which predominantly uses shades of white, where white symbolizes the purity of marriage. The character that appears in the interior design of this wedding house is elegant, graceful, clean, orderly and simple. With a combination of American style and character that emerges from each retail area, visitors can feel a different impression from other existing wedding services. This wedding house design includes retail areas such as consultation area, photography area, lighting area, bridal, salon, and accessories area.